A mitochondria-targeted fluorescent probe for the detection of endogenous SO2 derivatives in living cells. Issue 8 (27th February 2020) - Yan, Ye-Hao; Wu, Qiu-Rong; Che, Qiao-Ling; Ding, Man-Man; Xu, Min; Miao, Jun-Ying; Zhao, Bao-Xiang; Lin, Zhao-Min
Abstract : A unique fluorescent probe (ZACA) for the monitoring of SO2 derivatives was developed from coumarin and benzoindoles based on FRET and ICT. Abstract : A unique fluorescent probe (ZACA) for the monitoring of SO2 derivatives was developed from coumarin and benzoindoles based on FRET and ICT. ZACA exhibited an active emission signal, large Stokes shift, wide emission window distance, and high photostability. It also possessed many advantages in the ratiometric detection of HSO3 − /SO3 2− including low detection limit and high selectivity and sensitivity. Importantly, ZACA was successfully applied in the ratiometric detection of endogenous HSO3 − /SO3 2− in living cells with excellent cellular imaging capability (1 μM) and mitochondria-targeting ability (co-localization coefficient: 0.91).